One versus Two Venous Anastomoses in Microsurgical Free Flaps: A Meta-Analysis - Ahmadi, Iraj; Herle, Pradyumna; Rozen, Warren Matthew; Leong, James (Journal of Reconstructive Microsurgery, 2014)
Background Various reports suggest the augmentation of venous drainage through performing two venous anastomoses as a means of reducing the rate of thrombosis in free flap surgery. However, some suggest dual venous drainage may actually reduce venous blood flow velocity causing a potential risk for thrombosis.Methods  On the basis of the Preferred Reporting Items for Systematics Reviews and Meta-analysis statement, a systematic search was conducted using PubMed and Medline databases. A total of 12,190 articles relating to “free flaps” and “one versus two venous anastomoses” were found between January 1992 and November 2012. Of the 12,190 articles, 23 studies were included in a meta-analysis performed using STATA 11.2 (StrataCorp, College Station, TX). Studies with case control groups for both single and double venous anastomoses and clearly defined results for flap failure and venous thrombosis were included. 95% confidence interval (CI) were calculated for each study and pooled in both fixed and random-effects models for both flap failure and venous thrombosis events.Results The analysis shows a significant reduction in flap failure (risk ratio, 0.64; 95% CI, 0.41–0.99; p = 0.03) and venous thrombosis (risk ratio, 0.66; 95% CI, 0.46–0.97; p = 0.047) when performing two venous anastomoses compared with one in free flap surgery.Conclusion The results show that performing two venous anastomoses is associated with a reduction in the incidence of flap failure by 36% and venous thrombosis by 34% compared with one venous anastomoses. Given that the performing of an additional venous anastomoses confers a lower risk of complication and is technically feasible, where possible two venous anastomoses should be performed in free flap procedures, however, this should be decided on a flap by flap basis.
Keywords: venous anastomoses; one; two; single; dual